2012
DOI: 10.1161/circulationaha.111.030296
|View full text |Cite|
|
Sign up to set email alerts
|

9-Cis Retinoic Acid Promotes Lymphangiogenesis and Enhances Lymphatic Vessel Regeneration

Abstract: Background The lymphatic system plays a key role in tissue fluid homeostasis and lymphatic dysfunction due to genetic defects or lymphatic vessel obstruction can cause lymphedema, disfiguring tissue swellings often associated with fibrosis and recurrent infections without available cures to date. In this study, retinoic acids (RAs) were determined to be a potent therapeutic agent that is immediately applicable to reduce secondary lymphedema. Methods and Results We report that RAs promote proliferation, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 34 publications
1
103
0
Order By: Relevance
“…However, the results suggest that FGF2 is the primary factor involved in maintaining endothelial cell marker expression and plays a unique role in the suppression of mesenchymal markers expression in mLECs. Next, we confirmed that fibroblast growth factor receptors (FGFRs) are expressed in LECs at the mRNA level, as described previously (Cao et al, 2012;Choi et al, 2012;Kazenwadel et al, 2012;Matsuo et al, 2007;Shin et al, 2006). We checked FGFR expression by real-time RT-PCR, using mLECs cultured in EGM2, and pre-optimised TaqMan expression assays.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…However, the results suggest that FGF2 is the primary factor involved in maintaining endothelial cell marker expression and plays a unique role in the suppression of mesenchymal markers expression in mLECs. Next, we confirmed that fibroblast growth factor receptors (FGFRs) are expressed in LECs at the mRNA level, as described previously (Cao et al, 2012;Choi et al, 2012;Kazenwadel et al, 2012;Matsuo et al, 2007;Shin et al, 2006). We checked FGFR expression by real-time RT-PCR, using mLECs cultured in EGM2, and pre-optimised TaqMan expression assays.…”
Section: Resultsmentioning
confidence: 58%
“…2B). The lymphangiogenic activity of FGF2 has been demonstrated in vivo and in vitro (Cao et al, 2012;Chang et al, 2004;Choi et al, 2012;Kazenwadel et al, 2012;Kubo et al, 2002;Matsuo et al, 2007;Pepper et al, 1994;Shin et al, 2006), but the role of FGF2 in EndMT of LECs has not been studied previously. Therefore, we focused on the anti-EndMT activity of FGF2 in LECs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary LECs were cultured under the static or laminar flow condition for 12 hours and immediately subjected to ChIP as previously described (64) using anti-Klf4 antibody or control IgG. Sequences for the primers used are as follows: primer set 1: GAGCCTCCCAT-TACTCAGACC; GAGGCTCCCGCTTAGAAACT; primer set 2: TTGTTCTTTTGAGCCCTGCCATGTGAGTTC; CCTCCACCTGCT GCCTAAAGT).…”
Section: Methodsmentioning
confidence: 99%